Acinar cell density at the pancreatic resection margin is associated with post-pancreatectomy pancreatitis and the development of postoperative pancreatic fistula. Issue 5 (May 2018) - Nahm, Christopher B.; Brown, Kai M.; Townend, Philip J.; Colvin, Emily; Howell, Viive M.; Gill, Anthony J.; Connor, Saxon; Samra, Jaswinder S.; Mittal, Anubhav
Abstract: Background: There has been recent evidence supporting post-pancreatectomy pancreatitis as a factor in the development of postoperative pancreatic fistula (POPF). The aims of this study were to evaluate: (i) the correlation of the acinar cell density at the pancreatic resection margin with the intra-operative amylase concentration (IOAC) of peri-pancreatic fluid, postoperative pancreatitis, and POPF; and (ii) the association between postoperative pancreatitis on the first postoperative day and POPF. Methods: Consecutive patients who underwent pancreatic resection between June 2016 and July 2017 were included for analysis. Fluid for IOAC was collected, and amylase concentration was determined in drain fluid on postoperative days 1, 3, and 5. Serum amylase and lipase and urinary trypsinogen-2 concentrations were determined on the first postoperative day. Histology slides of the pancreatic resection margin were scored for acinar cell density. Results: Sixty-one patients were included in the analysis. Acinar cell density significantly correlated with IOAC (r = 0.566, p < 0.001), and was significantly associated with postoperative pancreatitis (p < 0.001), and POPF (p = 0.003). Postoperative pancreatitis was significantly associated with the development of POPF (OR 17.81, 95%CI 2.17–145.9, p = 0.001). Discussion: The development of POPF may involve a complex interaction between acinar cell density, immediate leakage of pancreatic fluid, and postoperative pancreatitis.